Supersymmetric 3-3-1 model - Montero, J. C. [UNESP]; Pleitez, V. [UNESP]; Rodriguez, M. C. [UNESP] (American Physical Society (APS), 2002)
We build a complete supersymmetric version of a 3-3-1 gauge model using the superfield formalism. We point out that a discrete symmetry, similar to R symmetry in the minimal supersymmetric standard model, is possible to be defined in this model. Hence we have both R-conserving and R-violating possibilities. Analysis of the mass spectrum of the neutral real scalar fields show that in this model the lightest scalar Higgs boson has a mass upper limit, and at the tree level it is 124.5 GeV for a given illustrative set of parameters. © 2002 The American Physical Society.